Long term outcomes of the Humeral Intracondylar Repair System for management of canine humeral intracondylar fissures and humeral condylar fractures - Hood, Rebecca S.; Walton, Myles Ben; Innes, John F. (Frontiers in Veterinary Science, 2024)
Objective To document long-term client-reported clinical outcomes and complications for the Humeral Intracondylar Repair System (HIRS) for treatment of humeral intracondylar fissures (HIF) and humeral condylar fractures (HCF) in dogs. Method Data collection involved the review of clinical records and analysis of an owner questionnaire regarding complication occurrence and client-reported outcome. The “Liverpool Osteoarthritis in Dogs” (LOAD) instrument was incorporated into the questionnaire. Results Twenty-six cases of HIF and 14 cases of HCF were included in the study, with follow-up times of over 12 months (range 13–97 months). Thirty-seven out of 40 cases reached long-term follow up: 25 out of 26 HIF cases, 11 out of 11 lateral condylar fracture cases and one out of three dicondylar fracture cases. Two cases of HIF suffered a gradual return of lameness in the long term; both dogs had concomitant medial coronoid disease. No other complications were reported in the long term. Excluding cases with concurrent issues affecting exercise, the median LOAD score at follow-up was 4 and 5 (out of 52) for HIF and HCF cases, respectively. At long-term follow-up, 36 out of 37 cases were reported to have regained “full function of the limb.” Clinical significance The results of this study, together with previously reported short and medium-term outcomes, support the use of HIRS for management of humeral intracondylar fissures and humeral condylar fractures.